Keabsahan Perjanjian Akibat Negative Confirmation Konsumen E-Commerce Perspektif Asas Al-Ridha - Nury Khoiril Jamil; Nisa Masitho; Agustine Rossa Diah Utari (Asy-Syari’ah : Jurnal Hukum Islam, 2024)
Transactions carried out via digital platforms have become unavoidable with the various features that are available and make it easier. However, on the one hand, if we look at the law of engagement, the majority of e-commerce platform providers apply standard contracts in carrying out transactions. Even though e-commerce provides effective facilities for complaints, returns and in-store inspections, it does not have a big impact on consumers, especially for transactions with small amounts. It is interesting to examine whether a negative assessment (negative confirmation) of the receipt of goods can still be said to be an agreement or the reason for the invalidation of the agreement from the perspective of the principle of al-ridha which is a fundamental principle in Islamic contract law. The method in this research uses normative juridical, this research approach uses legislation and conceptual. The results and recommendations of this research show that the principle of pacta sunt servanda in Indonesia is implemented strictly and cannot be intervened by anyone as long as it fulfills legal requirements and does not violate statutory regulations so that it meets legal certainty, but on the side of justice, especially in the perspective of the principle of al-ridha, It is necessary to take a substantive approach in assessing contracts, the validity and legal certainty of contracts is indeed necessary, but what is more important is the proportional value of justice.